2009
DOI: 10.3945/ajcn.2008.27131
|View full text |Cite
|
Sign up to set email alerts
|

Food sources of nitrates and nitrites: the physiologic context for potential health benefits

Abstract: The presence of nitrates and nitrites in food is associated with an increased risk of gastrointestinal cancer and, in infants, methemoglobinemia. Despite the physiologic roles for nitrate and nitrite in vascular and immune function, consideration of food sources of nitrates and nitrites as healthful dietary components has received little attention. Approximately 80% of dietary nitrates are derived from vegetable consumption; sources of nitrites include vegetables, fruit, and processed meats. Nitrites are produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
666
1
33

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 828 publications
(712 citation statements)
references
References 83 publications
12
666
1
33
Order By: Relevance
“…These findings are consistent with the emerging body of evidence to support improved vascular health following dietary NO 3 -supplementation (4-16 mmol·day -1 ) in younger [11][12][13] and older [16,17] normotensive adults, and in individuals with hypertension [18], peripheral artery disease [19] and heart failure [20]. Therefore, enriching the diet with NO 3 -, at a dose that can be readily achieved by a diet high in vegetables [4,7,9], might represent a practical and cost-effective intervention to lower cardiovascular disease morbidity and mortality.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…These findings are consistent with the emerging body of evidence to support improved vascular health following dietary NO 3 -supplementation (4-16 mmol·day -1 ) in younger [11][12][13] and older [16,17] normotensive adults, and in individuals with hypertension [18], peripheral artery disease [19] and heart failure [20]. Therefore, enriching the diet with NO 3 -, at a dose that can be readily achieved by a diet high in vegetables [4,7,9], might represent a practical and cost-effective intervention to lower cardiovascular disease morbidity and mortality.…”
Section: Introductionsupporting
confidence: 84%
“…It has been suggested that the cardio-protective effects of diets rich in fruit and vegetables might be linked to their high inorganic nitrate (NO 3 -) content [7][8][9]. Vegetable consumption accounts for 60-80% of dietary NO 3 -intake [10] with leafy-green vegetables (e.g., spinach and lettuce varieties) and beetroot being particularly rich in NO 3 - [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, human exposure to nitrite/nitrate comes mainly from the intake of processed food like cured meats, fishes and cheeses that are treated with nitrate salts (E251, E252) and nitrite salts (E249, E250) for preservation and/or organoleptic purposes. According to the EFSA recommendations (2006/52/EC), the amounts of nitrite/nitrate added 3 to several foodstuffs should be controlled, not exceeding 150 mg kg -1 of nitrite in the case of meat product [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that nitrate concentration at 600 to 700 ppm had a deleterious effect on rabbits' performance, but no attention was given to semen quality and litter traits. The adverse effect of nitrate was obvious with increasing nitrate intake in animals and humans (Shehata, 2005;DjekounBensoltane et al, 2007;Hord et al, 2009). Nitrate pollution -E-mail: attia0103753095@gmail.com could be increased because of agro-industry (Wahaab and Badawy, 2004;Burow et al, 2010).…”
Section: Introductionmentioning
confidence: 99%